(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2018)
Paper aims at studying the perception of investors towards mutual fund investment. The study is based on a sample of 380 respondents chosen using convenience sampling to understand the mutual fund buying behaviour of the individual investors. The paper determines various aspects of mutual funds which are considered by investors while investing in mutual fund. Aspects like reason for investment in mutual fund, preference of mutual fund are discussed.